Level of Consumers Awareness Regarding ISI, FPO & Agmark Standards - M.L. Bansal, Indu Karki, Neelam Mahrotra, (Indian Journal of Extension Education, 2022)
Every purchase involves the use of standards of, quantity, quality and value. A standard is a measuring stick, standardization includes the establishment of standards for sorting and grading of products to confirm these standards, packaging and labelling to give information to the readers about the grade and standard. Awareness regarding different standard marks of quality marks on food items is very crucial from the health point of consumers as non- standardized and fake products are now flooded in the market which are sold at low rate but are deteriorated enough in quality to harm the consumers, Hira (2003) reported that quality is the ultimate criterion of the desirability of any food product. Quality assurance is a very essential step in the process of product manufacturing in order to check the health hazards, which could occur after consuming the substandard or degraded food products.